A Clinical Study of Hollow Viscus Injuries in Abdominal Trauma (Indian Journal of Public Health Research & Development, 2022)
Background: Blunt abdominal trauma results in injury to the bowel and mesenteries in 3—5% of cases. The injuries arepolymorphic including hematoma, seromuscular tear, perforation, and ischemia. They preferentially involve the smallbowel and may result in bleeding and/or peritonitis. The main diagnostic challenge is to promptly and correctly identifyinjuries that require surgical repair.Objectives: To study the incidence, management and outcome of Hollow Viscus Injuries in Abdominal TraumaMethods: A comprehensive history was obtained from 50 patients attendants, including the patient’s demographiccharacteristics, the type of injury (whether blunt or penetrating), the symptoms with which the patient presented, and thetime elapsed from injury to admission. All patients underwent baseline tests such as haemoglobin, platelet count, bloodurea, blood glucose levels, serum electrolytes, and blood grouping. Ultrasound and CT scans of the abdomen were notperformed on all patients. Patients whose x-rays or clinical examinations were inconclusive had USG and CT scans.Results: Male predominance was observed with 72% and females were 28%. The male: female ratio was 2.57:1.Out of the50 cases with these kinds of injuries 56% of the cases underwent primary closure of perforation. 20% cases had resectionand anastomosis. 14% of the cases had Omental patch closure of perforation and 10% cases with serosal tear underwentsimple repairConclusion: Many predictors of morbidity and mortality have been identified, and treatment delays have been identifiedas a strong indication of morbidity that has a substantial impact on the post-operative path.
Keywords: Hollow viscus injury, trauma, blunt, Omental patch